CLOUD-BASED HEALTHCARE: INOVASI SISTEM INFORMASI MOBILE DENGAN FIREBASE SEBAGAI CLOUD DATABASE - Syaputra, Andhika; Ratnasari, Ratnasari (Jurnal Rekayasa Perangkat Lunak, 2025)
The development of information technology has driven the transformation of information systems in various sectors, including the health sector. One technology that is now widely used is Cloud Database, which allows online data storage and management without the need for physical storage media. This study discusses the application of Cloud Database using Firebase services in the development of a mobile-based Health Center Information System. The purpose of this study is to produce an information system that can improve the efficiency of services in the Health Center, especially in supporting recording, reporting, and service activities to the community more quickly and accurately. The method used in this study is Extreme Programming (XP) which emphasizes communication, feedback, and iterative software development. This study also uses the Unified Modeling Language (UML) approach for system modeling. The results of the study indicate that the use of Firebase as a Backend as a Service (BaaS) is effective in providing stable, secure, and easily integrated real-time database services with mobile applications. The system built is expected to be an alternative solution in the development of cloud-based health information systems in the future.